Regional disparities and the ways of their measurement: the case of the Visegrad Four countries - Tvrdoň, Michal; Skokan, Karel (Technological and Economic Development of Economy, 2011)
Real convergence of countries within European Union is measured mostly at the national level by the indicator of gross domestic product (GDP) per capita. Generally, countries with relatively low GDP per capita should catch-up with richer ones and this has become the main objective of post-communist countries at the beginning of the transition process. However, when we look at the regional level and regional GDP per capita data in these countries one can assume that the intensity of real convergence strongly differs among regions and disparities between regions still prevail. The paper attempts to identify factors responsible for persistence of regional disparities in the Visegrad Four countries. In the paper, available Eurostat NUTS 3 statistical data were used for analysis of economic disparities development in the Czech Republic, Hungary, Poland and Slovakia. The paper has two main parts. In the first theoretical part approaches to regional disparities and their measurement on the basis of indexes are provided. The second, empirical, part contains description of the main trends in regional development of Visegrad Four countries. This is followed by comparison of these trends in the Visegrad Four regions. Calculations suggested conclusion that the regional disparities between regions are growing. Article in English. Regioniniai skirtumai ir jų matavimo būdai: Keturių Vyšegrado šalių atvejis Santrauka. Tikroji Europos Sajungos šalių konvergencija nacionaliniu lygiu dažniausiai matuojama bendruoju vidaus produktu (BVP), tenkančiu vienam gyventojui. Apskritai pagrindinis pokomunistinių šalių tikslas pereinamojo proceso pradžioje – pasivyti turtingesnes šalis pagal BVP vienam gyventojui. Tačiau pažvelgus į duomenis, matyti, kad regioninių skirtumų vis dar yra. Straipsnyje siekiama nustatyti veiksnius, nuo kurių priklauso keturių Vyšegrado šalių regioniniai skirtumai. Šiame straipsnyje, naudojant ”Eurostat“ NUTS statistinius duomenis, buvo analizuojami Čekijos, Vengrijos, Lenkijos ir Slovakijos ekonominio vystymosi skirtumai. Straipsnis padalytas į dvi pagrindines dalis: pirmojoje dalyje išdėstyti regioninių skirtumų matavimo pagrindai, antrojoje, empirinėje, dalyje aprašomos pagrindinės keturių Vyšegrado šalių regioninės plėtros tendencijos. Šios tendencijos palygintos. Skaičiavimai atskleidė, kad regioniniai skirtumai didėja. Reikšminiai žodžiai: regioniniai skirtumai, Vyšegrado ketvertukas, statistinė analizė, BVP.